Development of BAPAU (manual book of long-distance training for bdk ambon employees) - Riana Antika Amahoroe (Balai Diklat Keagamaan Ambon, 2022)
Distance Training (PJJ) has become one of the training trends after the Covid-19 pandemic hit Indonesia. PJJ utilizes the Learning Management System (LMS) as a learning medium. Therefore, the researcher developed a BAPAU (Distance Training Handbook) for Ambon BDK Employees which explains in detail how to use the LMS, the functions of the features in the LMS and how to use them. The research used the Research and Development (R&D) method with the ADDIE model. 5 stages in the ADDIE model, namely the stages of Analysis (Analyze), Design (Design), Development (Development), Implementation (Implement) and the last stage, namely Evaluation (Evaluation). Based on the results of the development research that has been carried out, it can be concluded that the BAPAU for Ambon BDK Employees is very appropriate to use as a guide for PJJ.